DEVELOPMENT OF A SARS-COV-2 NEUTRALIZATION ASSAY SYSTEM USING PSEUDO-LENTIVIRUS - Armimi, Anastasia
COVID-19 is an acute respiratory disease outbreak caused by SARS-CoV-2 and has been declared a global pandemic. SARS-CoV-2 infects humans through the interaction of spike proteins that bind to the ACE2 receptor on target cells. This interaction is utilized in the development of a COVID-19 vaccine. Therefore, neutralizing antibodies are expected to form an adaptive immune system response. These antibodies work by binding to the virus to inhibit the virus's formation with the receptor. These antibodies can be detected through a neutralization assay. The gold standard of neutralization assay is carried out by microneutralization virus assay, which requires the wild-type virus. Therefore, using pseudovirus for the neutralization assay of SARS-CoV-2 is a safer alternative and can be carried out in BSL-2 laboratory facilities. This study aimed to develop a SARS-CoV-2 neutralization assay system using pseudo-lentivirus. The flow of this research includes characterization and confirmation of the plasmid used for pseudolentivirus production, determination of conditions for transfection and pseudolentivirus infection, and neutralization assay using the human serum. The condition of pseudo-lentivirus production was determined by choosing the transfection reagent type and adding centrifugation step at the time of harvesting the pseudolentivirus. Determining the conditions of pseudo-lentivirus infection was carried out by determining the target cell type and the number of pseudo-lentiviruses used for the neutralization test. Analysis of the success of pseudo-lentivirus infection was carried out by fluorescent assay and luciferase assay. The results showed that the plasmid used for pseudo-lentivirus production was characterized and confirmed and showed no mutations. The optimal conditions to produce the SARS-CoV-2 pseudo-lentiviruses were obtained using lipofectamine 2000 reagent and centrifugation during harvesting of the pseudo-lentivirus. Optimal pseudolentivirus infection conditions were obtained using puromycin-selected HEK 293TACE2 cells as target cells. The optimal number of pseudo-lentiviruses for neutralization assay was with an MOI of 0.075. The SARS-CoV-2 neutralization assay system using pseudo-lentivirus successfully detected neutralizing antibodies in human serum, which were indicated by a decrease in the percentage of infections.